PERSEPSI PENGGUNA LAYANAN KESEHATAN PRIMER MENGENAI KUALITAS PELAYANAN PADA PUSKESMAS BADAN LAYANAN UMUM DI KABUPATEN GIANYAR - Rina Listyowati; Putu Ayu Indrayathi; Ni Made Sri Nopiyani (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2016)
One of the reasons for establishing Public Service Agency (BLU) policy at Community Health Care Centers is the number of complaints for poor quality services. This policy was implemented in January 2010 by the Gianyar Government in every Community Health Care Center in Gianyar. This is the realization of the Gianyar Government's attention in improving the quality of the Community Health Care Center Services. This study aims to determine the public perception of the quality of services provided by the Community Health Care Center in Gianyar District. This study was a cross-sectional analytic study and conducted at four Community Health Care Centers with BLUD’s status in Gianyar District with 105 respondents selected by multistage random sampling method. The data collection included survey questionnaires and analyzed descriptively by chi square test. The results showed that overall the respondents had a